The association between four citation metrics and peer rankings of research influence of Australian researchers in six fields of public health. - Gemma Elizabeth Derrick (Public Library of Science (PLoS), 2011)
Doubt about the relevance, appropriateness and transparency of peer review has promoted the use of citation metrics as a viable adjunct or alternative in the assessment of research impact. It is also commonly acknowledged that research metrics will not replace peer review unless they are shown to correspond with the assessment of peers. This paper evaluates the relationship between researchers' influence as evaluated by their peers and various citation metrics representing different aspects of research output in 6 fields of public health in Australia. For four fields, the results showed a modest positive correlation between different research metrics and peer assessments of research influence. However, for two fields, tobacco and injury, negative or no correlations were found. This suggests a peer understanding of research influence within these fields differed from visibility in the mainstream, peer-reviewed scientific literature. This research therefore recommends the use of both peer review and metrics in a combined approach in assessing research influence. Future research evaluation frameworks intent on incorporating metrics should first analyse each field closely to determine what measures of research influence are valued highly by members of that research community. This will aid the development of comprehensive and relevant frameworks with which to fairly and transparently distribute research funds or approve promotion applications.